Educação CTSA e interdisciplinaridade : relações possíveis para a formação docente - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The constant transformations within the context of basic education impose significant challenges on teachers, who find themselves in a scenario marked by continuous transitions and increasing institutional demands. In this dynamic environment, guiding documents promote curricular changes aimed at integrating different areas of knowledge; however, teacher education remains predominantly organized in a disciplinary manner. As a result, teaching becomes fragmented, making it difficult for educators to adapt to the proposed changes. This reality undermines teacher autonomy and directly impacts their pedagogical practices, as well as the collective construction of knowledge in the lassroom. Given this panorama, the present research aimed to investigate the relationships among Science, Technology, Society, and Environment (STSE) education, interdisciplinarity, and continuing teacher education, seeking to answer the following guiding question: How can STSE Education promote interdisciplinary teaching practices among the Natural Sciences in high school? The general objective was to explore how in-service training grounded in the principles of STSE Education can contribute to the development of interdisciplinary pedagogical practices and encourage the construction of a didactic sequence that prioritizes collaborative and contextualized work in the teaching of the Natural Sciences. The specific objectives included: analyzing the presence of STSE Education in the normative documents of basic education, with a focus on the Natural Sciences and their Technologies, both at the national level and within the state of Goiás; identifying the principles of STSE Education that can contribute to overcoming the fragmentation of knowledge and promoting interdisciplinarity in these areas; investigating participating teachers’ prior conceptions of interdisciplinarity and STSE Education; and conducting a training workshop with teachers of Natural Sciences and their Technologies (NST), aimed at the collaborative development of an interdisciplinary didactic sequence based on STSE Education. To achieve these goals, a continuing education workshop was carried out with teachers from the areas of NST, Humanities, and Mathematics and its Technologies. Methodologically, the research is characterized as applied, with a qualitative and exploratory approach, structured around the principles of action research. Data analysis was conducted using the content analysis methodology proposed by Laurence Bardin. As part of this professional master’s dissertation, the resulting educational product consisted of the development of two materials: the Practical Guide for Planning Interdisciplinary Continuing Education Workshops for Teachers and the Practical Guide for Interdisciplinary Didactic Sequences. The latter was created collectively, based on the contributions of teachers who participated in the workshop, representing the outcome of a collaborative formative process. The initiative aimed to provide a space for reflection and knowledge exchange about interdisciplinary practices in the teaching of NST, promoting the integration of social aspects and encouraging the collaborative construction of contextualized teaching strategies. The theoretical foundation of the research was based on authors such as Hilton Japiassu (2016), Décio Auler (2007; 2011), Wildson L. P. dos Santos (2007; 2011; 2012), Paulo Marcelo Teixeira (2011; 2022; 2023), António Nóvoa (1992), and Paulo Freire (2022), among others. The results highlighted the relevance of STSE Education as a key axis for articulating interdisciplinary pedagogical practices, promoting a critical, reflective, and socially committed form of teaching. Moreover, the findings demonstrate the feasibility of integrating school subjects, contributing to the overcoming of curricular fragmentation and the development of more meaningful, contextualized, and humanized teaching strategies, anchored in the issues and challenges experienced by the participating school communities.
STS Education and Interdisciplinarity : possible connections for teacher education
Keywords: Práticas pedagógicas reflexivas; Formação continuada; Interdisciplinaridade; Reflective pedagogical practices; Continuing education; Interdisciplinarity; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::ENSINO-APRENDIZAGEM